2022
DOI: 10.1038/s41398-022-01862-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the ISR abrogates mGluR5-dependent long-term depression and spatial memory deficits in a rat model of Alzheimer’s disease

Abstract: Soluble amyloid-β-protein (Aβ) oligomers, a major hallmark of AD, trigger the integrated stress response (ISR) via multiple pathologies including neuronal hyperactivation, microvascular hypoxia, and neuroinflammation. Increasing eIF2α phosphorylation, the core event of ISR, facilitates metabotropic glutamate receptor (mGluR)-dependent long-term depression (LTD), and suppressing its phosphorylation has the opposite effect. Having found the facilitation of mGluR5-LTD by Aβ in live rats, we wondered if suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…The most important element of ISR signaling is eIF2α phosphorylation and increased expression of ATF4. The increase in P-eIF2α and ATF4 has been observed in many neurodegenerative diseases (Oliveira and Lourenco, 2016 ; Zhu et al, 2019 ; Ghadge et al, 2020 ; Chang et al, 2022 ; Hu et al, 2022 ). Our results also showed that the same result occurs in POCD mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most important element of ISR signaling is eIF2α phosphorylation and increased expression of ATF4. The increase in P-eIF2α and ATF4 has been observed in many neurodegenerative diseases (Oliveira and Lourenco, 2016 ; Zhu et al, 2019 ; Ghadge et al, 2020 ; Chang et al, 2022 ; Hu et al, 2022 ). Our results also showed that the same result occurs in POCD mice.…”
Section: Discussionmentioning
confidence: 98%
“…ATF4 then initiates a series of signaling cascades. Recent studies have suggested that ISR is involved in the pathogenesis of many neurodegenerative diseases (Chang et al, 2022 ), such as Alzheimer’s disease (Oliveira and Lourenco, 2016 ; Hu et al, 2022 ), amyotrophic lateral sclerosis (ALS; Ghadge et al, 2020 ), and Down syndrome (Zhu et al, 2019 ). It has been suggested that ISR had an important mechanistic connection with neurocognition (Pakos-Zebrucka et al, 2016 ), but the relationship between ISR and POCD is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…1:1 DMSO and PEG400 in saline was used as vehicle control. The choice of dose and timing of ISRIB administration was based on previous reports [42] and our study of the pharmacokinetics of ISRIB in live rats [44]. Four (Supplementary Figure 1).…”
Section: Western Blotmentioning
confidence: 99%
“…Increasing the ISR can facilitate mGluR-LTD [43,44] 104 while suppressing it has the opposite effect [43][44][45][46].…”
mentioning
confidence: 99%
“…Quantification of the protein expression was calculated with ImageJ (version 1.52a). The choice of dose and timing of ISRIB administration was based on previous reports (Krukowski et al, 2020) and our study of the pharmacokinetics of ISRIB in live rats (Hu et al, 2022). Four pair-housed relatively aged (17-18-month-old) rats received a single daily injection of ISRIB (2.5 mg/kg, i.p.)…”
Section: Western Blotmentioning
confidence: 99%